Horizon are we alone in the Universe - Bradshaw, Gideon (United States : BBC Active, 2006)
Scientists are searching space for planets and the possibility of life. The race is on to find life somewhere amongst the stars. Horizon follows the world's leading scientists in their search for a second Earth
Title from title screen
Editor, Andrew Cohen ; graphics, Jason White, Rob Chin ; sound, David Strayer ; camera Kevin White
Narration: Ian Holm
Keywords: Cosmology; Life on other planets